2000
DOI: 10.1007/pl00013419
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late-onset idiopathic focal segmental glomerulosclerosis

Abstract: Glomerular diseases in children, although similar in histological appearance to those in adults, may have a better prognosis. There is much controversy regarding the prognostic factors in idiopathic focal segmental glomerulosclerosis (FSGS), especially the comparative prognosis of children and adults. A comparative analysis was carried out of 36 consecutive biopsy-proven cases of idiopathic FSGS presenting early in life ['early onset' as seen in children < or =12 years (group I)] and 36 cases presenting later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…A number of cohort studies of FSGS in children [9,12,[24][25][26][27][28][29][30] and in adults [11,[31][32][33][34][35][36] has been reported in literature. Other studies have included both children and adults in the analysis [20,[37][38][39]. Nevertheless, few studies in the pediatric setting have investigated predictive factors of outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of cohort studies of FSGS in children [9,12,[24][25][26][27][28][29][30] and in adults [11,[31][32][33][34][35][36] has been reported in literature. Other studies have included both children and adults in the analysis [20,[37][38][39]. Nevertheless, few studies in the pediatric setting have investigated predictive factors of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The localization (vascular/tuft) and morphology (collapsing/cellular) of the changes were also determined. Other histological changes (mesangial cellularity, interstitial fibrosis, interstitial infiltration, tubular atrophy and blood vessel involvement) were scored according to a semiquantitative scoring system as follows: 0=no change, 1=focal changes, 2=mild involvement, 3=moderate changes, and 4=severe changes [20].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Yoshikawa et al [22] reported a percentage of segmentally sclerotic glomeruli ranging from 16-22% and a percentage of globally sclerotic glomeruli ranging from 8.4-14%. Series of adult patients with FSGS have shown a more severe glomerular involvement [13,32,33]. Histologic variants of FSGS have been regarded as predictors of the response to therapy and of clinical outcome in adult patients, although with conflicting results [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The localization (vascular/tubular) and morphology of the changes (collapsing/tip/cellular) were also determined. Other histological changes (mesangial matrix, mesangial cellularity, interstitial fibrosis, interstitial infiltration, tubular atrophy, and blood vessel involvement) were each scored according to a semi-quantitative scoring system as follows: 0=no change, 1=focal changes, 2=mild involvement, 3=moderate and 4=severe changes) [13]. Fifteen patients were submitted to two renal biopsies and previous histological findings were minimal change in six patients and mesangial proliferative changes in nine.…”
Section: Methodsmentioning
confidence: 99%
“…Other histopathological changes (mesangial matrix, mesangial cellularity, interstitial fibrosis, interstitial infiltration, tubular atrophy and blood vessel involvement) were scored using a semi-quantitative scoring system as follows: 0=no change; 1=focal changes (<10%); 2=mild involvement (10-25%); 3=moderate (26-50%); 4=severe changes (>50%). This system was similar to that used in an earlier study [15].…”
Section: Introductionmentioning
confidence: 95%